2015
DOI: 10.5114/wiitm.2015.54187
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of quality of life improvement after floppy Nissen fundoplication for gastroesophageal reflux disease.

Abstract: IntroductionGastroesophageal reflux disease (GERD) has a negative impact on global quality of life (QOL) of patients. In patients affected by GERD, laparoscopic Nissen fundoplication is one of the most commonly performed laparoscopic procedures worldwide.AimTo prospectively analyze the dynamics of QOL as well as severity of pain in patients with GERD, before and after laparoscopic floppy Nissen fundoplication.Material and methodsThe study involved 104 consecutive patients operated on for GERD in whom laparosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
2
9
0
1
Order By: Relevance
“…Different questionnaires, such as SF-36 and GERD-HRQL, have been used to evaluate potential improvement in quality of life in patients after anti-reflux surgery as a quality measure of the operation itself. It has been shown that quality of life improvement is gradual: achieving symptom relief 1 month after surgery, improvement in GI quality of life in 3 months after surgery, and improvement in general quality of life in the first year after surgery [ 6 , 53 ]. We found a significant decrease in the GERD-HRQL total score (2 (IQR 0–4.3) vs. 19 (IQR 17–32); p < 0.000) after modified LNF, proving a substantial increase in quality of life, confirming previous outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Different questionnaires, such as SF-36 and GERD-HRQL, have been used to evaluate potential improvement in quality of life in patients after anti-reflux surgery as a quality measure of the operation itself. It has been shown that quality of life improvement is gradual: achieving symptom relief 1 month after surgery, improvement in GI quality of life in 3 months after surgery, and improvement in general quality of life in the first year after surgery [ 6 , 53 ]. We found a significant decrease in the GERD-HRQL total score (2 (IQR 0–4.3) vs. 19 (IQR 17–32); p < 0.000) after modified LNF, proving a substantial increase in quality of life, confirming previous outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of this specific questionnaire results from its simplicity and transparency for patients and from our extensive experience with this QOL assessment tool. 18 The results of our study show a significant increase in all four domains of life (PWB, SWB, EWB, and FWB) after thoracic sympathectomy. The highest increase was observed in the functional domain, what can be comprehensible, as palmar hyperhidrosis mainly affects activities such as shaking hands or holding a pen, which are a part of patients' everyday functioning.…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, studies demonstrated that more than half of the patients had abnormal (> 4%) acid reflux in 24-h pH tests using PPI [ 19 ]. According to the literature and own experience, ARS seems to be the best way for long-term treatment of GERD and improving QoL [ 20 ].…”
Section: Discussionmentioning
confidence: 99%